Бегущий в ночи, или История одной любви: повесть / Воробей - Воробей Вера (Грамматика любви, 2005)
Экземпляры: ф.1 (2006) / Инвентарный номер: 49577 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4